Exploring causality between economic growth and air transport demand for Argentina and Uruguay - Brida, Juan Gabriel (2018)
This paper investigates the effects in the long-term between airtransportation and the economic growth in Uruguay and Argentina. Employingannual data from 1970 to 2011, the study uses cointegration analysis toconsider the existence of a long-run relation between real GDP and the numberof air passengers in each country. Results show that for both consideredcountries, the series are cointegrated and it is possible to estimate an errorcorrection model (ECM). The Granger causality test shows that causality goesunidirectionally from GDP to air-transport for both countries. The elasticity andimpulse-response function analysis shows that the effect of a GDP shock on thenumber of passengers is higher in Uruguay than in Argentina, which isconsistent with the characteristics of the air market and the geographicalconditions of each country. The results suggest different policy and planningimplications.